Digital imaging outperforms traditional scoring methods for spittlebug tolerance in Urochloa humidicola hybrids - Hernández, Luis Miguel; Espitia, Paula A.; Cardoso Arango, Juan Andrés (International Center for Tropical Agriculture, 2022)
American spittlebug species (Hemiptera: Cercopidae) are major pests in Urochloa humidicola (syn. Brachiaria humidicola) cultivars in the neotropics. The U. humidicola breeding program of the Alliance Bioversity-CIAT aims to increase tolerance to spittlebugs. To develop tolerant U. humidicola genotypes, adequate screening methods are needed. Currently, visual scores of plant damage by spittlebugs is the standard method to screen for variation in plant tolerance. However, visual scoring is prone to human bias, is of medium throughput and relies on the expertise of well-trained personnel. In this study, estimations of plant damage from SPAD chlorophyll meter measurements and digital images with visual scoring from an inexpert evaluator and visual scoring from an expert were compared. This information should inform if different methods could be implemented in the U. humidicola breeding program. Time needed to evaluate damage was recorded for each method. Lin’s correlation coefficient, Pearson’s correlation coefficient and broad sense heritability values were calculated. Damage estimated from digital images showed the highest throughput (twice as fast as visual scoring from an expert), high correlations with visual scoring (r>0.80, P<0.0001) and heritability values for plant damage as good or better (>0.7) than those obtained by visual scoring from an expert. Results indicate that digital imaging could improve the efficiency of phenotyping in breeding for increased tolerance to spittlebugs in U. humidicola.